2017
DOI: 10.1155/2017/9792363
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Drug-Drug Interaction in Ayder Comprehensive Specialized Hospital, Mekelle, Northern Ethiopia: A Retrospective Study

Abstract: Introduction Adverse drug interaction is a major cause of morbidity and mortality. Its occurrence is influenced by a multitude of factors. The influences of drug-drug interactions (DDIs) can be minimized through creation of awareness to health care professionals. Objective The objective of this study was to assess DDIs in Ayder Comprehensive Specialized Hospital (ACSH). Methodology A retrospective study design was employed on patient prescriptions available in the outpatient department of pharmacy and filled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
(21 reference statements)
1
15
0
1
Order By: Relevance
“…No of prescribed drugs (Polypharmacy) Patients taking three or more than three concomitant drugs are at higher risk of the occurrence of potential DDIs [27,28] There is an association of the occurrence of one or more potential DDIs with the number of medications prescribed per patient who took more than four medications [35] Polypharmacy (five or more medications) is an important factor which leads to potential DDIs [5, 29-31, 33, 34] Co-morbid disease Co-morbid condition independently increased the potential DDIs almost 2-folds [33] Age Older age was found to be predisposing factors for the occurrence of DDI [5,28,30,31] Potential DDIs were occurring more frequently in the age group of 2-6 years than any other age group of the pediatric population [29] Hospital stay The chance of taking multiple drugs increases with longer stays (greater than or equal to seven) in the hospital, which in turn increases the risk for potential DDIs [5] International Normalized ratio (INR value) Increase in international normalized ratio value was found to be strongly associated with DDI and hence the risk of bleeding [32] Footnote: Ten studies did not report the mechanisms of drug-drug interaction identifying actual DDIs is much more complicated than potential DDIs. The analysis showed that the occurrence of potential DDIs in the inpatient and outpatient settings reported by studies (inpatient: 73.2% (95% CI: 60.8 to 85.7%; outpatient: 80.0% (95% CI: 58.9 to 101.1%; inpatient and outpatient setting: 32.6% (95% CI: 30.6 to 34.6%).…”
Section: Factors Descriptionmentioning
confidence: 99%
“…No of prescribed drugs (Polypharmacy) Patients taking three or more than three concomitant drugs are at higher risk of the occurrence of potential DDIs [27,28] There is an association of the occurrence of one or more potential DDIs with the number of medications prescribed per patient who took more than four medications [35] Polypharmacy (five or more medications) is an important factor which leads to potential DDIs [5, 29-31, 33, 34] Co-morbid disease Co-morbid condition independently increased the potential DDIs almost 2-folds [33] Age Older age was found to be predisposing factors for the occurrence of DDI [5,28,30,31] Potential DDIs were occurring more frequently in the age group of 2-6 years than any other age group of the pediatric population [29] Hospital stay The chance of taking multiple drugs increases with longer stays (greater than or equal to seven) in the hospital, which in turn increases the risk for potential DDIs [5] International Normalized ratio (INR value) Increase in international normalized ratio value was found to be strongly associated with DDI and hence the risk of bleeding [32] Footnote: Ten studies did not report the mechanisms of drug-drug interaction identifying actual DDIs is much more complicated than potential DDIs. The analysis showed that the occurrence of potential DDIs in the inpatient and outpatient settings reported by studies (inpatient: 73.2% (95% CI: 60.8 to 85.7%; outpatient: 80.0% (95% CI: 58.9 to 101.1%; inpatient and outpatient setting: 32.6% (95% CI: 30.6 to 34.6%).…”
Section: Factors Descriptionmentioning
confidence: 99%
“…Pharmaceutical interaction is the interaction of incompatible drugs which occur outside of the body during mixing. 16 Studies indicated that there is an increased level of multiple medications and hence drug-drug interaction among the elderly part of the population. 3 The drug-drug interaction rate is higher in cardiovascular diseases compared to other disease.…”
Section: Introductionmentioning
confidence: 99%
“…WA also prepared the manuscript for publication. All authors have read and approved the manuscript Footnote: Seven studies did not report the mechanisms of drug-drug interaction Patients taking three or more than three concomitant drugs are at higher risk of the occurrence of potential DDIs [27,28] There is an association of the occurrence of one or more potential DDIs with the number of medications prescribed per patient who took more than four medications [35] Polypharmacy(five or more medications) is an important factor which leads to potential DDIs [5,29,30,31,33,34] Co-morbid disease Co-morbid condition independently increased the potential DDIs almost 2-folds [33] Age Older age was found to be predisposing factors for the occurrence of DDI [5,28,30,31] Potential DDIs were occurring more frequently in the age group of 2-6 years than any other age group of the pediatric population [29] Hospital stay The chance of taking multiple drugs increases with longer stays(greater than or equal to seven) in the hospital, which in turn increases the risk for potential DDIs [5] International Normalized ratio (INR value) Increase in international normalized ratio value was found to be strongly associated with DDI and hence the risk of bleeding [32] Footnote: Ten studies did not report the mechanisms of drug-drug interaction Forest plot depicting the pooled prevalence of moderate potential DDIs of 14 studies in Ethiopian Hospitals Figure 5 Forest plot depicting the pooled prevalence of minor potential DDIs of 14 studies in Ethiopian Hospitals Figure 6 Subgroup analysis of the prevalence of potential DDIs based on region…”
Section: Resultsmentioning
confidence: 99%
“…Different studies were also supported as polypharmacy and comorbid disease increases the likelihood of the occurrence of potential DDIs [15,33,42,43]. In the review, taking ve or more medications was an important factor that leads to potential DDIs [5,29,30,31,33,34]. This may be due to the probability of taking interacting drugs is increased.…”
Section: Discussionmentioning
confidence: 97%